2003
DOI: 10.1046/j.1462-2920.2003.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraradical mycelium of the arbuscular mycorrhizal fungus Glomus lamellosum can take up, accumulate and translocate radiocaesium under root‐organ culture conditions

Abstract: Radiocaesium enters the food chain when plants absorb it from soil, in a process that is strongly dependent on soil properties and plant and microbial species. Among the microbial species, arbuscular mycorrhizal (AM) fungi are obligate symbionts that colonize the root cortex of many plants and develop an extraradical mycelial (ERM) network that ramifies in the soil. Despite the well-known involvement of this ERM network in mineral nutrition and uptake of some heavy metals, only limited data are available on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 34 publications
4
35
1
Order By: Relevance
“…Cs uptake and translocation by an AMF have been demonstrated in vitro with root organ cultures in which carrier-free 134 Cs was added to a liquid medium with a very low concentration of K (6). This system precludes the verification of transfer from fungus to host plant due to the lack of shoots and the difficulties associated with precise localization of Cs, which may be contained exclusively within intraradical fungal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Cs uptake and translocation by an AMF have been demonstrated in vitro with root organ cultures in which carrier-free 134 Cs was added to a liquid medium with a very low concentration of K (6). This system precludes the verification of transfer from fungus to host plant due to the lack of shoots and the difficulties associated with precise localization of Cs, which may be contained exclusively within intraradical fungal structures.…”
Section: Discussionmentioning
confidence: 99%
“…AMF have been introduced into phytoremediation of soil contaminated with radionuclides to enhance plat resistance and capacity to accumulate radionuclides. Declerck et al demonstrated that the extraradical hyphal network of AMF incorporate and translocate radiocaesium from a radiocaesium labelled root-free compartment to a root compartment, using a monoxenic multicompartment growing system 18 . De Boulois et al suggested that there was the possibility, although limited, of radiocaesium accumulation in the intraradical mycelium 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of AM fungi in Cs acquisition and accumulation by plants were also investigated, but most often yielded contradictory results (see [10] and references therein).…”
Section: Role Of Mycorhizal Fungi In Radiocaesium Accumulation In Plantmentioning
confidence: 99%
“…In 2003 [10], Declerck et al unambiguously demonstrated that AM fungi could take up and translocate Cs in vitro using the two-compartment system of Rufyikiri et al [5] (see above). The total uptake of Cs represented 1.5% of the initial Cs present in the hyphal compartment (HC).…”
Section: Role Of Mycorhizal Fungi In Radiocaesium Accumulation In Plantmentioning
confidence: 99%